Application of bilateral crossing C2 laminar screws and screw placement assistant tools for upper cervical spine fixation: technology note - Qi, Hongfei; Feng, Haoxuan; Li, Zhong; Li, Ming; Wu, Bo; Zhang, Chengcheng; Liu, Shichang (Frontiers in Surgery, 2025)
BackgroundAxial lamina screw placement is a new posterior cervical fixation technique that differs from the previously described transarticular screw placement and pedicle screw placement in terms of the risk of causing damage to the vertebral artery. However, the previously reported laminar screw placement technique carries the risk of causing damaging to the screws in the inner wall of the vertebral plate and screw protrusion into the spinal canal. To address this issue, our center has designed a screw placement assistant tool to help surgeons safely insert screws.MethodsThe medical records of 6 patients with upper cervical spine injuries who were admitted to Xi'an Honghui Hospital between March 2021 and February 2022 were retrospectively analyzed to assess the patients' postoperative recovery. Self-designed screw placement assistants were used to insert double cortical laminar screws for posterior cervical fixation. Computed tomography (CT) scanning was performed to observe screw placement after surgery. The clinical and postoperative recovery data of the patients were reviewed, and the clinical efficacy of aids for bicortical screw placement in the axial (C2) vertebral lamina were evaluated.ResultsAll patients were followed up for 9–16 months, with an average of 11.5 months. The fractures were satisfactorily fixed and healed. No patients experienced wound infection, internal fixation failure, or secondary surgery. Postoperative CT scans showed that a total of 12 C2 bicortical lamina screws were implanted in 6 patients. The axial lamina screws were well positioned and located in the center of the axial lamina, without any deviation or detachment. There were also no cases in which screws penetrated the medial cortical bone of the lamina or protruded into the spinal canal. No patients experienced vertebral artery injury.ConclusionsC2 laminar screw placement, as a technique for posterior fixation of the high cervical spine, can be a good choice when transarticular screw and pedicle screw placement are difficult. Our designed screw placement assistance tool can help surgeons safely and accurately insert bicortical cross screws into the axial vertebral lamina, avoiding screw damage to the inner wall of the lamina and spinal canal.